OIL AND GAS ECONOMY IN UZBEKISTAN: TRANSITION TO SUSTAINABLE USE OF HYDROCARBON RESOURCES - Taraxtiyeva , Kulmira (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
Uzbekistan, one of the largest economies in Central Asia, is a transition economy significantly dependent on the oil and gas sector. This article analyzes the current state of Uzbekistan’s oil and gas economy, its political-institutional environment, and strategic opportunities for sustainable development. The study is based on a mixed-methodological approach, including quantitative data analysis (2019–2024), policy document review, and stakeholder consultations. The results show that the sector contributes approximately 20% of state budget revenues; however, excessive dependence on hydrocarbon exports, aging capital assets, and low energy efficiency remain major challenges. The article proposes a multifaceted strategic framework aimed at economic diversification, transition to renewable energy sources, acceleration of privatization, and the use of digital transformation tools.